Laparoscopic Dismembered Pyeloplasty in a Solitary Kidney with Intrarenal Pelvis: Two Challenges in One Case. (26th November 2017) - Amasyali, Akin Soner; Ates, Erhan; Kazici, Hakan Görkem; Manav, Alper Nesip; Erol, Haluk
Abstract : Laparoscopic pyeloplasty (LP) for ureteropelvic junction obstruction (UPJO) is one of the most appropriate surgical techniques to achieve the optimal goal of minimally invasive surgery. However, urologists hesitate to use the laparoscopic approach in UPJO with solitary kidney or intrarenal pelvis. There are a few published studies on laparoscopic pyeloplasty cases in intrarenal pelvis. However, to the best of our knowledge, the present case is the first in the literature in terms of intrarenal pelvis in a solitary kidney. Generally, YV plasty is the accepted technique instead of dismembered pyeloplasty in UPJO with small or intrarenal pelvis. However, in this report, we showed that dismembered LP can be performed with good results in intrarenal pelvis UPJO, even if it is in the solitary kidney.